Relationship between the molecular diversity of plasmids, antibiotic resistance and virulence genes of Staphylococcus aureus isolates from private hospitals in Gauteng, South Africa - Ehlers, M.M. (Marthie Magdaleen) (University of Pretoria, 2025)
Dissertation (MSc (Medical Microbiology))--University of Pretoria, 2024.